Efecto de la aplicación de Ca y Si en el desarrollo radicular y el crecimiento inicial del cultivo de banano en Chanduy, Santa Elena, Ecuador - Méndez Tomalá, Héctor Alexis (2025)
The province of Santa Elena (PSE) is considered an emerging area in banana cultivation, with little scientific information on management under the specific climatic, edaphic and limiting conditions of the area. This highlights the importance of conducting studies to potentiate the crop, in this sense, an investigation was conducted to evaluate the effect of Ca and Si application on root development and initial growth of the banana crop between February and July 2024. The trial was carried out under a completely randomized block design (CRBD) with a bifactorial structure, including two evaluation factors; A (Si) and B (Ca) with three doses each, nine treatments and four replicates were obtained. The data were analyzed using the Infostat statistical package. Parametric statistics were used for the variables that met the assumptions of analysis of variance, using Tukey's test at 95 % confidence. Under another scenario, the non-parametric variables were analyzed by general linear and mixed model, where the Fischer's LSD test was used at 95 %. The data suggest that treatment 4, where Si was used at a dose of 248.8 mg L-1 , achieved the best results in root mass, percentage of live root, height and diameter of pseudostem in mother and daughter plants, chlorophyll intensity, number of leaves and age at flowering. In addition, it was positive that the Si treatments showed greater resistance to climatic variations. Regarding nutrient content in the soil and petiole, no differences were found; however, it was observed that the values were higher in the petiole as the dose of Si increased. It is concluded that the application of Si stimulates root development, improves plant vigor and attenuates environmental stress.